Combination of iLux Photothermal Pulsation Therapy with 0.05% Cyclosporine in the Treatment of Meibomian Gland Dysfunction: A Clinical Study - Xu H; Kang Q (International Journal of General Medicine, 2025)
Hongliang Xu, Qian Kang Department of Ophthalmology, Aidi Eye Hospital, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Qian Kang, Department of Ophthalmology, Aidi Eye Hospital, No. 41.43.45, West Second Section, Second Ring Road, Qingyang District, Chengdu, 610031, Sichuan, People’s Republic of China, Email Xu_hongliang12@163.comObjective: The aim of this study is to investigate the effect of iLux with 0.05% cyclosporine in the treatment of meibomian gland dysfunction.Methods and Materials: In retrospective analysis, 72 patients of meibomian gland dysfunction were selected and divided into combination groups according to different treatment methods (n=32, iLux + 0.05% cyclosporine ophthalmic fluid) and the conventional group (n=44, 0.05% cyclosporine ophthalmic fluid). Compare the two groups of baseline data and clinical efficacy difference, compare the two groups after treatment eye symptoms, eye surface disease index score change.Results: Overall response rate of the combined group was higher than the conventional group (P < 0.05). Post-treatment, both groups were improved differently (P < 0.05), however, in the combined group, ocular symptom score, ocular surface disease index, conjunctival congestion score, corneal fluorescent staining score, meibomian gland (ostium condition score, lipid secretion shape score, deletion score) and interleukin-6, interleukin-1 β were all lower than those in the conventional group, The non-invasive mean tear film break-up time (NIBUTav), non-invasive first tear film break-up time (NIBUTf) and tear meniscus height in the combined group were higher than the conventional group (P < 0.05).Conclusion: ILux meibomian gland photothermal pulsation complex therapy instrument combined with 0.05% cyclosporine ophthalmic solution for the treatment of meibomian gland dysfunction.Keywords: meibomian gland dysfunction, iLux eyelid gland photothermal pulsatile compound therapy instrument, cyclosporine ophthalmic solution, treatment effect, patients